Quality Improvement Project to Reduce Unnecessary Chest X-ray in a Tertiary Center - M. Abdoun; Reham Babiker; Abdelmoneim Mahgoub (Dr. Sulaiman Al Habib Medical Journal)
The proper diagnostic approach for acute bronchiolitis is one of the significant controversial aspects among clinicians in the pediatric field. The radiographic evaluation of the classic presentation has a limited role and may expose patients to unnecessary procedures. Despite the presence of evidence-based guidelines, unnecessary radiography is still well documented worldwide. Therefore, our aim was primarily to evaluate the frequency of chest x-ray abnormalities in acute bronchiolitis and under what circumstances changes are accurately expected. The secondary aim was to decrease the use of unnecessary chest x-rays in acute bronchiolitis. For this, a retrospective study was conducted on 150 patients who were younger than 2 years of age and admitted for acute bronchiolitis. Patients with underlying comorbidities were excluded from the study. The results showed nonspecific alternation of chest radiography consistent with the disease behavior in 83.3% of the cases. There was no significant correlation between the clinical variables and the severity of radiological findings in our study. The study demonstrated that 59.3% of chest x-rays were not indicated and the majority of the overall requests were for high-grade fever. We conclude that there is no proven value of routine radiography in the usual presentation. In agreement with previous research, we recommend that requests should be made for particular indications as per existing guidelines. Ongoing education and re-auditing of practice continue to expand this body of evidence.